Modeling and Position Control of Fiber Braided Bending Actuator Using Embedded System - Mohd Nizar Muhammad Nasir, Mohd Nizar Muhammad Nasir; Najaa Aimi Mohd Nordin, Najaa Aimi Mohd Nordin; Ahmad Athif Mohd Faudzi, Ahmad Athif Mohd Faudzi; Mohamed Naji Muftah, Mohamed Naji Muftah; Mohd Akmal Mhd Yusoff, Mohd Akmal Mhd Yusoff; Shahrol Mohamaddan, Shahrol Mohamaddan (Mdpi, 2023)
The System identification (SI) black box method is used in this study to obtain the mathematical model of a fiber braided bending actuator (FBBA) using MATLAB Simulink. Data from the system input and output are used by the black box method. Thus, the voltage supplied to the electro-pneumatic regulators and the position (angle) of the FBBA system are used to collect input–output data in this study. In the system, PRBS generators are used to generate an input signal for the electro-pneumatic valve. The auto-regressive with exogenous input (ARX) model is chosen. As the controller for the FBBA position system, PID with the Genetic Algorithm (GA) tuning method and auto-tuned tuning method is proposed. The reference angle, simulation, and actual test are compared. The mathematical model gained from the SI method is verified through the simulation and test result of the position control. It was found that the model obtained through SI able represent the actual plant.